2019
DOI: 10.1038/s41467-019-10497-2
|View full text |Cite
|
Sign up to set email alerts
|

Modeling microcephaly with cerebral organoids reveals a WDR62–CEP170–KIF2A pathway promoting cilium disassembly in neural progenitors

Abstract: Primary microcephaly is caused by mutations in genes encoding centrosomal proteins including WDR62 and KIF2A. However, mechanisms underlying human microcephaly remain elusive. By creating mutant mice and human cerebral organoids, here we found that WDR62 deletion resulted in a reduction in the size of mouse brains and organoids due to the disruption of neural progenitor cells (NPCs), including outer radial glia (oRG). WDR62 ablation led to retarded cilium disassembly, long cilium, and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
157
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(164 citation statements)
references
References 50 publications
6
157
1
Order By: Relevance
“…Dual Smad signaling inhibitors were used in neural induction medium to enhance neuroepithelial expansion (Kadoshima et al 2013). Embryoid bodies (EBs) were added into droplets of Geltrex to enhance complex tissue formation, followed by the growth in a spinning bioreactor to facilitate oxygen exchange and nutrient absorption (Zhang et al 2019). To directly compare RAB39b mutant and isogenic controls in organoid formation, equal numbers (∼9000 starting cells) of dissociated single PSCs were used to generate EBs, which resulted in no differences in morphology or surface areas at culture day 12.…”
Section: Rab39b Mutant Cerebral Organoids Model Human Macroocephalymentioning
confidence: 99%
See 2 more Smart Citations
“…Dual Smad signaling inhibitors were used in neural induction medium to enhance neuroepithelial expansion (Kadoshima et al 2013). Embryoid bodies (EBs) were added into droplets of Geltrex to enhance complex tissue formation, followed by the growth in a spinning bioreactor to facilitate oxygen exchange and nutrient absorption (Zhang et al 2019). To directly compare RAB39b mutant and isogenic controls in organoid formation, equal numbers (∼9000 starting cells) of dissociated single PSCs were used to generate EBs, which resulted in no differences in morphology or surface areas at culture day 12.…”
Section: Rab39b Mutant Cerebral Organoids Model Human Macroocephalymentioning
confidence: 99%
“…5A). We quantified the relative thicknesses of SOX2-positive VZ layers according to published methods (Zhang et al 2019). Statistical analysis showed that mutant organoids had a substantial increase of SOX2-positive VZ thickness at weeks 4, 6, and 8 ( Fig.…”
Section: Rab39b Deletion Increases Proliferation and Expansion Of Npcsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, deciliation has also been reported as a predominant mode of ciliary disassembly during cell cycle progression in mammalian cells [15]. Defect in ciliary resorption has been shown to inhibit G1-S transition and delays cell cycle progression [16][17][18][19][20], which leads to premature differentiation of neural progenitors [18,20,21]. Several studies also suggest that ciliary disassembly is related to tumorigenesis because primary cilia are disassembled in a variety of cancer types [22].…”
Section: Introductionmentioning
confidence: 99%
“…KIF2A, a MT (microtubule)-depolymerizing kinesin, functions in mitotic spindle assembly 11 and primary cilium disassembly in mitotic cells 12,13 and in axonal pruning in differentiating neurons 14,15 . Recent studies have suggested that KIF2A alternative splicing is regulated by neuron-specific RNA-binding proteins 16 and its isoform abundance dynamically shifts during the neural progenitor-to-neuron transition during development of the cerebral cortex 3 .…”
Section: Introductionmentioning
confidence: 99%